HES6 drives a critical AR transcriptional programme to induce castration‐resistant prostate cancer through activation of an E2F1‐mediated cell cycle network - Ramos‐Montoya, Antonio; Lamb, Alastair D; Russell, Roslin; Carroll, Thomas; Jurmeister, Sarah; Galeano‐Dalmau, Nuria; Massie, Charlie E; Boren, Joan; Bon, Helene; Theodorou, Vasiliki; Vias, Maria; Shaw, Greg L; et al. (EMBO molecular medicine, 2014)
Castrate‐resistant prostate cancer (CRPC) is poorly characterized and heterogeneous and while the androgen receptor (AR) is of singular importance, other factors such as c‐Myc and the E2F family also play a role in later stage disease. HES6 is a transcription co‐factor associated with stem cell characteristics in neural tissue. Here we show that HES6 is up‐regulated in aggressive human prostate cancer and drives castration‐resistant tumour growth in the absence of ligand binding by enhancing the transcriptional activity of the AR, which is preferentially directed to a regulatory network enriched for transcription factors such as E2F1. In the clinical setting, we have uncovered a HES6‐associated signature that predicts poor outcome in prostate cancer, which can be pharmacologically targeted by inhibition of PLK1 with restoration of sensitivity to castration. We have therefore shown for the first time the critical role of HES6 in the development of CRPC and identified its potential in patient‐specific therapeutic strategies. Synopsis HES6 promotes castration resistance, maintains AR chromatin binding at a subset of sites in the absence of hormone stimulation and predicts poor outcome after prostatectomy. Inhibition of HES6‐responsive gene PLK1 enhances anti‐androgen sensitivity. HES6 promotes castration resistance in prostate cancer cells. HES6 maintains AR chromatin binding at a subset of sites in the absence of hormone stimulation. HES6‐associated genes predict poor clinical outcome after radical prostatectomy. HES6‐responsive gene PLK1 is highly expressed in a new hormone relapse TMA. Inhibition of PLK1 enhances sensitivity to anti‐androgens. Graphical Abstract HES6 promotes castration resistance, maintains AR chromatin binding at a subset of sites in the absence of hormone stimulation and predicts poor outcome after prostatectomy. Inhibition of HES6‐responsive gene PLK1 enhances anti‐androgen sensitivity.